+0  
 
0
77
1
avatar+83 

Solve the system of equations

 Nov 27, 2018

Best Answer 

 #1
avatar+16286 
+3

ADD the two equations together to get

9x = 27

x=3           Sub this in to either of the equations to find y

 

3(3) - y = 6

9-y=6

9-6 = y

y = 3

 Nov 27, 2018
 #1
avatar+16286 
+3
Best Answer

ADD the two equations together to get

9x = 27

x=3           Sub this in to either of the equations to find y

 

3(3) - y = 6

9-y=6

9-6 = y

y = 3

ElectricPavlov Nov 27, 2018

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.